A bird that flies with two wings : the kastom and state justice systems in Vanuatu - Forsyth, Miranda (ANU E Press, 2009)
"This book investigates the problems and possibilities of plural legal orders through an in-depth study of the relationship between the state and customary justice systems in Vanuatu. It argues that there is a need to move away from the current state-centric approach to law reform in the South Pacific region, and instead include all state and non-state legal orders in development strategies and dialogue. The book also presents a typology of models of engagement between state and non-state legal systems, and describes a process for analysing which of these models would be most advantageous for any country in the South Pacific region, and beyond"--Publisher's description